Immunomodulatory Effects of Hemagglutinin- (HA-) Modified A20 B-Cell Lymphoma Expanded as a Brain Tumor on Adoptively Transferred HA-Specific CD4+ T Cells - Valentin P. Shichkin; Roman M. Moriev (The Scientific World Journal)
Previously, the mouse A20 B-cell lymphoma engineered to express hemagglutinin (HA) antigen (A20HA) was used as a systemic tumor model. In this work, we used the A20HA cells as a brain tumor. HA-specific CD4+ T cells were transferred intravenously in a tail vein 5 days after A20HA intracranial inoculation and analyzed on days 2, 9, and 16 after the adoptive transfer by different methods. The transferred cells demonstrated state of activation as early as day 2 after the adoptive transfer and most the of viable HA-specific cells became anergic on day 16. Additionally, symptoms of systemic immunosuppression were observed in mice with massive brain tumors at a late stage of the brain tumor progression (days 20–24 after the A20HA inoculation). Despite that, a deal of HA-specific CD4+ T cells kept the functional activity even at the late stage of A20HA tumor growth. The activated HA-specific CD4+ T cells were found also in the brain of brain-tumor-bearing mice. These cells were still responding to reactivation with HA-peptide in vitro. Our data support an idea about sufficient role of both the tumor-specific and -nonspecific mechanisms inducing immunosuppression in cancer patients.